THE SURVEY OF ENVIRONMENTAL STRATEGY ON INDONESIA CORPORATIONS: A REPLICATION MODEL - Ranto P. Sihombing; Monika Palupi; Stephana Dyah Ayu; Vena Purnamasari (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
Environmental damage occurs at this time pushed corporations to change their business strategy into environmental strategy. Hence, performance measurement system is also used toward environmental. The Result of research conducted by Perego and Hartman (2009) has found relationship between environmental strategy and the use of performance measures mediated by performance measurement system (PMS). Based on the limitation of study conducted by Perego and Hartman (2009), this study replicate and meliorate by distributing questionnaires to corporate social responsibility (CSR) division of corporations in Indonesia. Because this division is part of the corporations, they are considered to understand more on the company's policy on social and environmental. Research of this study found that relationship between environmental strategy and the use of performance measurement system mediated manager sensitivity to environment and degree of congruity. Keywords: environmental strategy, uses performance measurement, company policy, sensitivity, congruity.